2014
DOI: 10.1111/joss.12119
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Sweetness Profile of MNEI and Comparison with Commercial Sweeteners

Abstract: None of the current sweeteners match sucrose in terms of sweet taste quality or temporal characteristics. In fact, the sensory performance of a sweetener changes over time and it could interact with other stimuli. Time-intensity (t-I) and temporal of dominance sensation (TDS) are both dynamic sensory methods, but they give different and complementary information: t-I focuses on the evolution of the intensity of one attribute, whereas TDS is a descriptive multi-attribute methodology that deals with the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 27 publications
7
34
4
1
Order By: Relevance
“…Analysis of variance results (Table ) showed that the sweeteners did not differ for almost every parameter extracted from the t – I curves ( I start , I end , I max , t start , t SPl , t EPl ) ( p > 0.05), except for t end ( p ≪ 0.01), which ranged between 42 and 50 s, for xylitol, sucrose, and sorbitol, without significant differences among these sweeteners, to 66 s, for MNEI. These results indicate that the sweetness imparted by MNEI ended almost 20 s later compared to the other sweeteners in stirred yogurts, hinting to a different mechanism of interaction between the protein and sweet taste receptors, already underlined in previous studies (Di Monaco et al, ; Leone et al, ; Miele, Cabisidan, Galiñanes Plaza, et al, ).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Analysis of variance results (Table ) showed that the sweeteners did not differ for almost every parameter extracted from the t – I curves ( I start , I end , I max , t start , t SPl , t EPl ) ( p > 0.05), except for t end ( p ≪ 0.01), which ranged between 42 and 50 s, for xylitol, sucrose, and sorbitol, without significant differences among these sweeteners, to 66 s, for MNEI. These results indicate that the sweetness imparted by MNEI ended almost 20 s later compared to the other sweeteners in stirred yogurts, hinting to a different mechanism of interaction between the protein and sweet taste receptors, already underlined in previous studies (Di Monaco et al, ; Leone et al, ; Miele, Cabisidan, Galiñanes Plaza, et al, ).…”
Section: Resultssupporting
confidence: 61%
“…For what concerns, its sweetness temporal profile and its lingering sweet taste were already reported for sweet proteins, both MNEI (Di Monaco et al, ) and thaumatin (Asakura et al, ), and it is due to a strong interaction of these proteins with the taste buds. This property could negatively affect consumer liking; therefore, it should be avoided or reduced in some way, even if it should be verified.…”
Section: Resultsmentioning
confidence: 88%
“…The MNEI, mutant single‐chain monellin, was produced in E. Coli and purified, following the experimental protocol of Rega et al ().As gelling agent agar powder E406 (A.C.E.F s.p.a., Fiorenzuola d'Arda, Italy) was used. Simple gel samples were prepared at three agar concentrations (1, 1.5, and 2% w/w) for each sweetener, at the iso‐sweet concentration, according to Di Monaco et al () (Table ). Agar powder was dispersed in water at 90°C, agitated through a magnetic stirrer (Mod F60, FALC Instruments s.r.l., Italy) at 3.5 rpm and heated up to 95°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have performed several studies (Di Monaco et al, ; Di Monaco, Miele, Volpe, Picone, & Cavella, ; Rega et al, ) to characterize the sweetness perception of MNEI protein and to compare it with commercial sweeteners, focusing on MNEI sweetness in liquid matrix. However, since both sweeteners and hydrocolloids are largely used ingredients in food industry, contributing to both functional and sensory properties, it is necessary to extend these studies to semisolid or solid media.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal profiles of currently used non-nutritive sweeteners are not consistent with that of sucrose [12]. When investigating the temporal profiles of sensory attributes (i.e., sweetness) of water solutions and beverages, the measurement method used most frequently is a time-intensity evaluation [13,14].…”
Section: Introductionmentioning
confidence: 99%